Current technical surgical practice of emergency appendicectomy: a cross-sectional survey of surgical registrars in the UK - Currow, C (Ann R Coll Surg Engl, 2020)
INTRODUCTION: Appendicectomy remains one of the most commonly performed procedures in general surgery. The aim of this study was to explore variation in operative techniques of an appendicectomy among surgical registrars in England. MATERIALS AND METHODS: An anonymised survey was sent out to surgical registrars in the UK via email and social media. Subgroup analyses were performed comparing respondents based on their level of seniority and subspecialty background. RESULTS: A total of 168 respondents completed the survey, of whom 77.4% (130/168) were specialty trainees years 3–8 and 44.6% (75/168) were colorectal trainees. The majority (98.8%) preferred a laparoscopic approach to appendicectomy. Overall, 73.2% opted to use diathermy to divide an uninflamed mesoappendix. Half of the respondents (50%) preferentially used diathermy to control the appendicular artery, followed by 44% preferring use of metal or polymeric clips. The appendicular stump was most often secured with Endoloops (85.7%) when removing a macroscopically uninflamed appendix but less readily used in the visibly inflamed appendix (75.6%, p = 0.01). Colorectal and upper gastrointestinal registrars were more likely to use diathermy on the mucosa of the appendix stump compared with other subspecialties (p = 0.03). The majority (82.1%) of respondents extracted the appendix via a retrieval bag. Regarding skin closure, most respondents (69%) adopted absorbable subcuticular sutures. Preferential duration of postoperative antibiotic use following appendicectomy for complicated appendicitis varied among the respondents. CONCLUSION: There are similarities and differences across surgical registrars in terms of technical practice in appendicectomy, partially attributed to prior experience and training.